The Experimental Analysis of Predictive Control Scheme in High Frequency Gate Driver Design - Muhammad Amin Bin Ab Latif, Muhammad Amin (Universiti Teknologi Petronas, 2010)
Predictive Dead Time Control Scheme is used in gate driver to overcome the problems relating to the td. This control scheme applies the prediction concept based on the feedback output from the circuit to predict and reduce the tdon the switching cycle of the gate driver. Therefore by using the application of the predictive dead time control scheme, the problem related with the td can be minimized.